Pendampingan SDI Al-Mashduqie Menuju Sekolah Adiwiyata Berbasis Pertanian Berkelanjutan - Zuhriyah, Amanatuz; Tripatmasari, Mustika; Triadjie, Haryo; Widodo, Slamet (Jurnal Ilmiah Pangabdhi, 2023)
Concern for environmental problems is needed from an early age. Environmental education in schools through the Caring and Cultured Environment program in schools (PBLHS) is one of the efforts to shape the environmental behavior of the younger generation. SDI Al-Mashduqie does not yet have programs related to environmental education and 'adiwiyata schools'. The aim of this community-based empowerment is to implement the PBLHS movement which is realized in the 'Adiwiyata School'. This activity was carried out with the participation of students, teachers, principals and student guardians who are expected to provide environmental insights for all school members. The existing conditions show that there is no specific policy regarding the environment that is applied in schools. Learning about the environment in the curriculum is integrated with several subjects and there is no involvement of external parties in environmental preservation activities. Increased knowledge was obtained after conducting education related to adiwiyata, especially regarding environmental care and waste management, as well as using several technologies to support a green and healthy environment in the form of redesigning school landscapes, hydroponic training, biofloc catfish cultivation and socialization related to energy conservation by using solar electricity.